Current Perspective on Fiberglass Posts Length: Finite Element Study - Cruzado-Oliva, Fredy Hugo; Vega-Anticona, Alexander; Ortiz-Diaz, David Arturo; Alarco-Jurado, Luisfelipe Carlos; Arbildo-Vega, Heber Isac (Odovtos - International Journal of Dental Sciences, 2024)
The literature to date has not reported a clear consensus on the optimal length of fiberglass posts for efficient clinical performance when restoring endodontically treated maxillary incisors with severe crown destruction. This study aimed to determine the stress distribution of fiberglass posts at different lengths using finite element analysis. Five 3D finite element models (groups A-E) were created, each representing a restoration system for endodontically treated maxillary central incisors. The models included post-core crowns with crown-root ratios of 1/3, 1/2, 2/3, 4/5, and 1/1. A static load of 100N force was applied to the palatal surface at 45º to the long axis of the tooth. Von Mises values and | maximum stresses in the crown, dentin, resin cement, and post-core were evaluated separately. The maximum stress experienced was A < C < B < E < D. Von Mises stresses were located in the upper and middle buccal thirds and in the apical palatal third of post A, as well as the upper and middle buccal thirds in posts B, C, D, and E. The lowest distribution of maximum and Von Mises stresses was observed in model A.